2019
DOI: 10.3390/app9061215
|View full text |Cite
|
Sign up to set email alerts
|

Probability Analysis of Hypertension-Related Symptoms Based on XGBoost and Clustering Algorithm

Abstract: In this paper, cluster analysis and the XGBoost method are used to analyze the related symptoms of various types of young hypertensive patients, and finally guide patients to target treatment. Hypertension is a chronic disease that is common worldwide. The incidence of it is increasing, and the age level of patients is decreasing year by year. Effective treatment of youth hypertension has become a problem in the world. In this paper, young hypertension patients are classified into two groups by cluster analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Additionally, the underlying relationship between variables was assumed to be non-linear. For such cases the literature supports [40][41][42][43][44][45][46][47] using gradient tree boosting and deep learning methods for better prediction results.…”
Section: Covariatesmentioning
confidence: 99%
“…Additionally, the underlying relationship between variables was assumed to be non-linear. For such cases the literature supports [40][41][42][43][44][45][46][47] using gradient tree boosting and deep learning methods for better prediction results.…”
Section: Covariatesmentioning
confidence: 99%
“…Since its inception [29], the Extreme Gradient Boost (XGBoost) has been the favourite technique used to address the challenge of classification prediction in the medical area. By utilizing XGBoost, many researchers addressed various subtopic in the health/medical field such as diagnoses [5], [8], [30]- [34], related diseases [4] [6], [9], [34], [35], medical treatment [36], [37], patient status [12], [14], [16], [38], or event genomic [39].…”
Section: Related Workmentioning
confidence: 99%
“…A research conducted an experimental study using XGBoost Classifiers with some scenarios such as transformation, resampling, clustering, and ensemble learning to predict the diagnosis of second primary cancers (SPCs) [30] The resampling and clustering strategies were used to determine the best method used to identify some important risk factors associated with SPCs in patients with breast cancer. The combination of the XGBoost and Clustering analysis approach was also proposed by [8] to predict the hypertensionrelated symptoms from 531 hypertensive patients data in a hospital in Beijing. These combination techniques showed that there are significant differences in symptomatic entropy between patients with type II and type I hypertension.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…W. Change et al in their manuscript entitled "Probability analysis of hypertension-related symptoms based on XGBoost and clustering algorithm" [16] proposed a clustering based XGBoost algorithm to classify type I and type II hypertension. Moreover, studies showed that symptoms of ventricular hypertrophy, arteriosclerosis and microalbuminuria are more prone to occur for type II hypertension sufferers.…”
Section: Workmentioning
confidence: 99%